Endocrine resistant breast cancer: brain metastasis - Matthew Willman; Jonathan Willman; Brandon Lucke-Wold (Open Exploration Publishing Inc., 2022)
Endocrine resistant breast cancer metastasis continues to serve as a significant clinical challenge with high morbidity and mortality for patients. As the number of breast cancer cases continues to rise, the rate of brain metastasis has also increased. For single lesions or a large symptomatic lesion with other smaller lesions, surgical resection is a viable option in non-eloquent regions. Stereotactic radiosurgery is a great option for post-operative therapy or for 10 or fewer small lesions (< 3 cm in size). Whole-brain radiation can be used sparingly for large tumor burdens but should encompass hippocampus sparing techniques. Chemotherapy options have remained relatively limited due to decreased permeability of the blood-brain barrier. Emerging monoclonal antibody treatments have offered initial promise, especially for endocrine resistant breast cancer metastasis.